Pendidikan Nilai Agama Dan Moral Anak Melalui Kegiatan Bermain Sains - Rahmawati, Riyas; Sumedi, Sumedi (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2020)
This research used qualitative research type has descriptive analitical characteristic. This location of research used was Kindergarten School ABA Margokaton 2 Seyegan, Sleman, Yogyakarta. The data collection was conducted by conducting involved observation, in-depth interview and documentation. Data analysis was conducted by giving meaning towards data of which has been succesfully collected and from the data was drawn conclusion. The result of research was education of religion and moral value through science playing activity in Kindergarten School ABA Margokaton 2 Seyegan by using 5 important components, i.e.: Religionity, Sociality, Trusthworthily, Reponsibility, and Environmental Awareness. Meanwhile the methods used were 8, i.e.: Experiment Method, Demonstration Method, Story-Telling Method, Questioning-Answering Method, Job Tour Method, Singing Method, Project Method, and Task Providing Method. The factor influecing education of religion value and moral value in Kindergarten School ABA Margokaton 2 are: (a) Supporting Factor is influenced by: school environment, teacher, and friend, (b) Impeding Factor is influenced by: lack of coordination between teacher and parent, familial environment, social environment, and advancement of technology.